Art in the bark: Indigenous carved boab trees (Adansonia gregorii) in north-west Australia. (December 2022) - O'Connor, Sue; Balme, Jane; Frederick, Ursula; Garstone, Brenda; Bedford, Rhys; Bedford, Jodie; Rivers, Anne; Bedford, Angeline; Lewis, Darrell
Abstract: Abstract : Found only in a restricted area of north-west Australia, the Australian boab ( Adansonia gregorii ) is recognisable by its massive, bottle-shaped trunk, and is an economically important species for Indigenous Australians, with the pith, seeds and young roots all eaten. Many of these trees are also culturally significant and are sometimes carved with images and symbols. The authors discuss the history of research into carved boabs in Australia, and present a recent survey to locate and record these trees in the remote Tanami Desert. Their results provide insight into the archaeological and anthropological significance of dendroglyphs in this region and add to a growing corpus of information on culturally modified trees globally.